2019
DOI: 10.1136/openhrt-2018-000933
|View full text |Cite
|
Sign up to set email alerts
|

Statistical ranking of electromechanical dyssynchrony parameters for CRT

Abstract: ObjectiveMechanical evaluation of dyssynchrony by echocardiography has not replaced ECG in routine cardiac resynchronisation therapy (CRT) evaluation because of its complexity and lack of reproducibility. The objective of this study was to evaluate the potential correlations between electromechanical parameters (atrioventricular, interventricular and intraventricular from the dyssynchrony model presented in 2000), their ability to describe dyssynchrony and their potential use in resynchrony.Methods455 sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…that LPEI was the one correlated with the greatest number of other parameters, 13 out of 17. 18 A decrease of LPEI was associated with directionally similar changes of the other parameters indicating improved synchrony. We found that a 16 ms decrease in LPEI was the optimal cut-off for predicting CRT response at 6 months.…”
Section: Discussionmentioning
confidence: 84%
“…that LPEI was the one correlated with the greatest number of other parameters, 13 out of 17. 18 A decrease of LPEI was associated with directionally similar changes of the other parameters indicating improved synchrony. We found that a 16 ms decrease in LPEI was the optimal cut-off for predicting CRT response at 6 months.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, we performed a sensivity analysis (Table 1) on the mechanical model using a Latin Hypercube Sampling method, coupled with the computation of the Partial Ranked Correlation Coefficient [9] for a collection of relevant model outputs, selected from [2].…”
Section: Bestel-clement-sorine Modelmentioning
confidence: 99%